Integrated development plans of the functional urban areas in Pomeranian region in Poland - Sołtys, Jacek; Golędzinowska, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The European Commission put a growing emphasis on the territorial and integrated approach to policy support addressed in the frame of regional policy. In a special way this process refers to cities along with their functional environment. In Poland the National Spatial Development Concept 2030 has introduced the concept of functional areas, among others – Functional Urban Areas (FUAs). There is also a new tool – Integrated Territorial Investment (ITI) – for FUAs in the EU programming perspective of 2014-2020. The scope of the article includes FUAs of regional and sub-regional centers in Pomeranian Voivodeship. The objectives of this paper are: to identify the diversity of projects planned for FUAs; to identify factors that integrate the projects mentioned above. The following main methods have been applied: analysis of documents; typology of projects proposed for implementation concerning their subject and integrating factors. Territorial agreements basing on regional operational program were a formula of development planning in the researched FUAs, more liberal than the formula of ITI. In 95% projects integrating factors can be identified (as hypothesis) and classified. The projects relate to many fields, the most to energy efficiency, health and transport
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 30-38
Keywords: functional urban areas; integrating factors; integrated territorial investment; Pomeranian Voivodeship; typology; funkcjonalne obszary miejskie; czynniki integrujące; zintegrowane inwestycje terytorialne; województwo pomorskie; typologia